Esthetic lip repositioning: A cosmetic approach for correction of gummy smile - A case series - Asha Ramesh; Radha Vellayappan; Sheethalan Ravi; Kaarthikeyan Gurumoorthy (Wolters Kluwer Medknow Publications, 2019)
Gummy smile has been a prevalent esthetic disorder commonly affecting younger individuals due to various causes such as skeletal, dento-alveolar, or soft-tissue origin. It can be due to jaw deformities, altered passive eruption, or tooth malpositioning. Usually, the corrective measures incorporate orthognathic surgery and orthodontic treatment. Orthognathic surgery results in significant morbidity and hospitalization. Lip repositioning can be employed as an alternative cosmetic treatment modality for the correction of an excessive gingival display with minimal risk or side effects. Although there are many articles existing in the literature on this topic, a series of three cases is unique in demonstrating the esthetic smile enhancement in an orthodontic patient and also a combination of lip-repositioning technique and laser-assisted crown lengthening in vertical maxillary excess cases. This case series also showed the predictability of lip-repositioning technique with a follow-up of 2 years.